Implementation of Drone-Based Monitoring for Work at Height Operations in the Petrochemical Industry: A Case Study at PT XYZ - Priambodo Galih Puspito; Aufaclav Zatu Kusuma Frisky (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Work-at-height activities in the petrochemical industry involve significant occupational safety risks due to PPE non-compliance, unsafe behavior, and limitations of conventional monitoring systems. Objective: This study aimed to evaluate the effectiveness of drone-based safety monitoring in improving Full Body Harness compliance, reducing unsafe behavior, and decreasing occupational risks during work-at-height activities. Method: A field-based quasi-experimental pre-test-post-test design was conducted over four months using structured observations, drone-based visual documentation, paired-sample t-test, Cohen’s d effect size, and Fine-Kinney risk assessment. Result and Discussion: Drone implementation reduced Full Body Harness violations from 23 to 9 cases (60.87% reduction) and unsafe behavior from 12 to 6 cases (50% reduction). Statistical analysis confirmed significant improvements in PPE compliance (p = 0.004; Cohen’s d = 1.50) and unsafe behavior (p = 0.020; Cohen’s d = 1.06). Fine-Kinney assessment showed that monitoring risks decreased from 900 (Very High Risk) to 18 (Acceptable Risk) for elevated structure observation and from 540 (Very High Risk) to 30 (Possible Risk) for lifting operations. Conclusions: Drone-based safety monitoring effectively improves safety behavior, enhances monitoring effectiveness, and reduces occupational risks during work-at-height activities in the petrochemical industry